An Experimental and Numerical Investigation of Photovoltaic Module Temperature Under Varying Environmental Conditions. Issue 3 (21st February 2021) - Jaszczur, Marek; Teneta, Janusz; Hassan, Qusay; Majewska, Ewelina; Hanus, Robert
Abstract: The photovoltaic module temperature depends on many parameters and becomes an important parameter from the system efficiency point of view. For this reason, in this research, a comprehensive analysis of the photovoltaic modules has been done using in-situ experimental measurement and computer simulation. The objective of the current work is to model the fluid flow and heat transfer from a photovoltaic module, by means of three-dimensional numerical simulation to determine the module temperature. The photovoltaic module with the variable inclination was subjected to variable environmental and operating conditions. The results of the analysis show that module temperature isn't only ambient temperature and solar radiation dependent like what is taken into account by many models but also depends on wind speed and wind direction. It has been found that the mounting conditions which are not taken into consideration by most of the literature models, play an important role and only this fact may introduce an additional increase in module temperature about 10–15 °C and may decrease module efficiency more them 4-6.5%. The results that were obtained enable the development of a model for the photovoltaic module temperature caused by the environmental conditions as well as mounting conditions.